A case study of radiative forcing upon a tropical cloud cluster - Byrd, Gregory P., author; Cox, Stephen K., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1980)
Tropospheric radiative convergence profiles from Cox and Griffith (1978) are used to assess the radiative forcing upon a tropical cloud cluster located in the vicinity of the GATE A/B-scale array during 4-6 September 1974. "Slab" and cross sectional analyses are carried out in order to present a three dimensional view of the radiative convergence field within the cluster and its surrounding regions. Next, a simple vertical motion profile is constructed to investigate the potential effects of radiative forcing upon cluster scale dynamical interactions with the large scale circulation. The model is tested on a daytime and a nighttime case within the cluster life cycle. The ensuing discussion evaluates the analysis and expands upon the possible roles of radiative forcing upon cluster scale and large-scale dynamics. Radiative forcing is strongest during the initial stages of cluster development. Throughout the cluster life cycle, the radiative forcing is consistently strongest in the middle troposphere (400-700 mb). With the intensification of the cluster system, a substantial weakening of horizontal gradients of radiative convergence occurs as a result of SW warming superimposed upon LW cooling during the daylight hours. Increased amounts of middle and high cloud remnants in regions surrounding the maturing cluster also contribute to the observed weakening of radiative forcing. The cross sectional analyses reveal that E-W gradients of radiative convergence between the cluster and its surroundings are comparable in magnitude to the N-S gradients. The maximum in cluster precipitation intensity is observed to lag the incidence of strong radiative forcing by some 6-8 hours, in general agreement with GATE composite observations. Continental-oceanic differential heating plays a significant role in modulating the cluster and large scale dynamical interactions, accounting for-the anomalously large precipitation lag observable in the GATE cluster. The radiatively derived vertical motion model yields a qualitatively realistic total area of cluster influence for the nighttime period. The model assumption of a closed mass system breaks down during the daytime period, yielding an unreasonably large total area of influence. This suggests the occurrence of significant cluster scale interactions with large scale circulations during the daytime period. Radiative forcing appears to play a more significant role in dynamical interactions at night, when circulations appear to be somewhat more localized.
November, 1980.
Keywords: Clouds -- Tropics